TINGKAH LAKU KAWIN ENTOG CIAYUMAJAKUNING PADA SYSTEM PEMELIHARAAN INTENSIF - Dini Widianingrum; Tuti Widjastuti; Asep Anang; Iwan Setiawan (Fakultas Pertanian Universitas Majalengka, 2021)
Muscovy duck development can be influenced by reproductive performance, including mating behavior. The purpose of the study was to obtain the quantitative characteristics of the Ciayumajakuning Muscovy duck mating and to obtain the best antog in its mating characteristics. The research method was carried out experimentally using a completely randomized design with 4 treatments and 5 replications. The parameters observed were mating frequency, mating duration, mating time, and mating location. The results showed that the quantitative characteristics of the antog Kuningan showed a significant difference in the frequency of mating with the drake and duck and the duration of mating was higher than that of the Cirebon, Indramayu, and Majalengka Muscovy duck. This is supported by data on the frequency of mating with 7.4 drake and duck 2 times/day, and the mating duration is 119.4 seconds. The mating time of the Cirebon, Indramayu, Majalengka, and Kuningan Muscovy duck did not show a significant difference, namely more in the first and second quarters at 06.01-12.00 WIB and 12.01-16.00 WIB. The mating location is in zone 1 in the area near the place of feed and drinking water. In conclusion, Muscovy duck Kuningan has the best marital characteristics.